2017
DOI: 10.29207/resti.v1i3.70
|View full text |Cite
|
Sign up to set email alerts
|

Metode DSRM Dalam Pelaksanaan dan Penatausahaan Alokasi Dana Desa

Abstract: The use of village funds allocation is an integral part of the village financial use which includes planning, implementation Keywords: Village Fund Allocation, DRSM, Use of Village Funds, Unified Model Language AbstrakPenggunaan alokasi dana desa merupakan bagian tidak terpisahkan dari pengunaan keuangan desa yang meliputi perencanaan, pelaksanaan, penatausahaan, pelaporan, dan pertanggung jawaban. Oleh sebab itu pemerintahan desa harus mampu mengelola secara transparan, akuntabel, dan bebas dari penyalahgunaa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The research method used in this research is Design Science Research Methodology (DSRM) which includes 7 sequential steps, namely: the study of literature, determination of research objectives, identification of problems, design solutions, making prototype applications (prototyping), demo, documentation and publications [5] . DSRM is a research methodology that is widely used in research related to software development and applied applications, such Pratama and Arisna https://doi.org/10.51630/ijes.v3i2.38 31 as developing village fund applications [6] and developing data collection systems for migrants based on Hybrid Cloud [7] . The seven sequential steps at Design Science Research Methodology (DSRM) are shown in Fig.…”
Section: Design Science Research Methodology (Dsrm)mentioning
confidence: 99%
“…The research method used in this research is Design Science Research Methodology (DSRM) which includes 7 sequential steps, namely: the study of literature, determination of research objectives, identification of problems, design solutions, making prototype applications (prototyping), demo, documentation and publications [5] . DSRM is a research methodology that is widely used in research related to software development and applied applications, such Pratama and Arisna https://doi.org/10.51630/ijes.v3i2.38 31 as developing village fund applications [6] and developing data collection systems for migrants based on Hybrid Cloud [7] . The seven sequential steps at Design Science Research Methodology (DSRM) are shown in Fig.…”
Section: Design Science Research Methodology (Dsrm)mentioning
confidence: 99%
“…Metode yang digunakan penulis dalam merancang sistem informasi akuntansi siklus pendapatan adalah Design Science Research Methodology (DSRM). DSRM adalah panduan standar untuk penelitian yang terkait dengan desain sebuah layanan dalam bentuk sistem informasi [11]. Metode DSRM ini akan melakukan pendekatan dengan tujuan menciptakan serta melakukan evaluasi terhadap suatu desain sistem dalam mengatasi masalah yang cukup kompleks [12].…”
Section: Siklus Pendapatanunclassified
“…DSRM with 7 sequential stepsFrom Figure1. above, DSRM was introduced by Peffers, et al, which includes seven research steps, namely: a study of literature, determine of research objectives, identification of the problem, design solutions, making prototype application (prototyping), demo, documentation and publication[27][28][29][30]. The literature study was carried out through the collection of several pieces of literature related to the Covid19 case in Bali Province as well as several uses of the CBR method and AI as state of the art.…”
mentioning
confidence: 99%